A Natural Impact: NK Cells at the Intersection of Cancer and HIV Disease - Lucar, Olivier; Reeves, R. Keith; Jost, Stephanie (Frontiers in Immunology, 2019)
Despite efficient suppression of plasma viremia in people living with HIV (PLWH) on cART, evidence of HIV-induced immunosuppression remains, and normally benign and opportunistic pathogens become major sources of co-morbidities, including virus-induced cancers. In fact, cancer remains a primary cause of death even in virally suppressed PLWH. Natural killer (NK) cells provide rapid early responses to HIV infection, contribute substantially to disease modulation and vaccine protection, and are also major therapeutic targets for cancer immunotherapy. However, much like other lymphocyte populations, recent burgeoning evidence suggests that in chronic conditions like HIV, NK cells can become functionally exhausted with impaired cytotoxic function, altered cytokine production and impaired antibody-dependent cell-mediated cytotoxicity. Recent work suggests functional anergy is likely due to low-level ongoing virus replication, increased inflammatory cytokines, or increased presence of MHClow target cells. Indeed, HIV-induced loss of NK cell-mediated control of lytic EBV infection has been specifically shown to cause lymphoma and also increases replication of CMV. In this review, we will discuss current understanding of NK cell modulation of HIV disease, reciprocal exhaustion of NK cells, and how this may impact increased cancer incidences and prospects for NK cell-targeted immunotherapies. Finally, we will review the most recent evidence supporting adaptive functions of NK cells and highlight the potential of adaptive NK cells for cancer immunotherapy.